THE USE OF TRANSLATION TECHNIQUES IN SUBTITLING THE DHAUP AGENG DOCUMENTARY MOVIE - Budiana, Agnes Arum; Sutopo, Djoko; Rukmini, Dwi (Universitas Negeri Semarang, 2017)
Translation plays an important role in learning foreign language. Translating, however, is not an easy task because each language has its own rules in phonetic, structure and word. In order to achieve the equivalence, there are some techniques involved in translation process. This study was to analyze the use of translation techniques in subtitling the Dhaup Ageng documentary movie, to find out which translation techniques were mostly used and to investigate the ways in which the translation techniques were used. This study used descriptive-qualitative approach to describe the results of the analysis of translation techniques. The object of the study was the subtitle of Dhaup Ageng documentary movie which consist of 77 utterances of Sri Sultan Hamengkubuwono X. The findings indicated that literal translation was applied in 19 excerpts, compression was in 13 excerpts, borrowing was in 9 excerpts, transposition was in 8 excerpts, linguistic amplification was in 7 excerpts, amplification was in 4 excerpts, compensation was in 3 excerpts, calque, established equivalent and reduction were applied in 2 excerpts, while adaptation, description, discursive creation, generalization, modulation, substitution, particularization and variation were applied in 1 excerpt. Based on the results, literal translation was the most dominant technique used in subtitling process. It might be used properly if the context required the use of such technique.